1982
DOI: 10.1152/jappl.1982.52.4.976
|View full text |Cite
|
Sign up to set email alerts
|

Central and regional circulatory adaptations to one-leg training

Abstract: Six young healthy male subjects performed submaximal and maximal exercise on bicycle ergometers with one leg and two legs before and after 8 wk of one-leg training with each of both legs. The following variables were measured during one- and two-leg exercise: oxygen uptake, heart rate, mean arterial blood pressure, cardiac output, leg blood flow, and iliac arteriovenous differences for oxygen and lactate. After training the maximal oxygen uptake during one- and two-leg exercise was increased by 19 and 11%, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
140
1
7

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(180 citation statements)
references
References 0 publications
24
140
1
7
Order By: Relevance
“…First, within both individual muscles and muscle groups, both oxygen uptake and maximum aerobic force production are consistently greater when the exercise engages a lesser total mass of muscle (5,15,50,53). Previous results from the many one-vs. two-legged cycle ergometry and knee-extension studies indicate greater aerobic force production occurs via higher rates of oxygen uptake in the working muscle (35,51), rather than through the recruitment of synergist muscles. Supporting this, during onelegged knee-extensions neuromuscular activity has been found to be absent in synergistic muscle groups at work rates up to the aerobic maximum (5).…”
Section: Discussionmentioning
confidence: 95%
“…First, within both individual muscles and muscle groups, both oxygen uptake and maximum aerobic force production are consistently greater when the exercise engages a lesser total mass of muscle (5,15,50,53). Previous results from the many one-vs. two-legged cycle ergometry and knee-extension studies indicate greater aerobic force production occurs via higher rates of oxygen uptake in the working muscle (35,51), rather than through the recruitment of synergist muscles. Supporting this, during onelegged knee-extensions neuromuscular activity has been found to be absent in synergistic muscle groups at work rates up to the aerobic maximum (5).…”
Section: Discussionmentioning
confidence: 95%
“…Ceretelli et al (1984) have shown that the xenon clearance method may underestimate muscle blood flow by as much as 2-fold. From the results reported by Clausen and associates (Clausen, Klausen, Rasmussen & Trap-Jensen, 1973;Secher, Clausen, Klausen, Noer & Trap-Jensen, 1977;Klausen et al 1982) it appears that when a large percentage of the muscle mass is involved in the exercise (arm work added to leg work or two-legged instead of one-legged exercise) resistance in vessels of the exercising limbs is also increased.…”
Section: Discussionmentioning
confidence: 99%
“…However, most tracer-dilution methods are not directly applicable to the present study. Some of the concerns we had were that in flow measurements using bolus injections of tracer or cold saline (Hosie, 1962;Jorfeldt, Juhlin-Dannfelt, Pernow & Wassen, 1978;S0rlie & Myhre, 1977;Klausen, Secher, Clausen, Hartling & Trap-Jensen, 1982) one obvious general problem is the fluctuations in blood flow during dynamic exercise. Multiple randomized measurements which are averaged may compensate for this.…”
Section: Discussionmentioning
confidence: 99%
“…The knee extension exercise allows isolation of a specific muscle group (quadriceps), which appears to be particularly susceptible to age-related loss of oxidative capacity (Conley et al 2000). As in the present study, the single-limb training model has been used to differentiate between effects due to O 2 transport and those due to O 2 utilisation and/or diffusion of O 2 from the capillaries to the mitochondria (Davies & Sargeant, 1975;Saltin et al 1976;Henriksson, 1977;Thomas et al 1981;Klausen et al 1982;Hardman et al 1987) although none of these studies have examined on-transient V O 2 kinetics. The advantage of using older subjects, with slow initial V O 2 kinetics, is that larger changes in V O 2 kinetics are elicited with training (Babcock et al 1994b), and thus it is easier to determine the relative importance of oxygen delivery versus utilisation in determining V O 2 kinetics.…”
mentioning
confidence: 99%